Blangsinga gianyar waterfall tourism object. current destinations that are hits in bali - Firlie Lanovia Amir; Gusti Ngurah Yoga Semadi (Journal of Business on Hospitality and Tourism, 2021)
In Bali, in particular, more and more tourist attractions are made for the development of tourist areas that have not been touched by tourists. This tourist destination is undeniably a place to compete to visit. New destinations are always popping up on the island of Bali. One of the contemporary tourist destinations that is now crowded with tourists is Blangsinga Gianyar Waterfall. You could say, this now popular waterfall is a new but old destination. The reason is because this waterfall was popularly known as Tegenungan Waterfall. Research related to the development strategy of Blangsinga waterfall tourism. Blangsinga Waterfall is actually the same waterfall as Tegenungan Waterfall. The difference in the two names is only obtained because of the login access used. The name Tegenungan is attached to this waterfall because it passes through Banjar Tegenungan. Similar conditions are also used because of the use of access via Blangsinga Village. Its development is very necessary in the context of the existence of these tourist destinations. One of the efforts made by Blangsinga Village as a tourist village is the preservation of the Kecak dance which has begun to recede amidst the rampant competition for the Kecak dance in Bali. Creative activities carried out by village officials by involving local communities in the effort to preserve the Blangsinga Kecak dance which was staged at the Blangsinga waterfall is a new breakthrough in order to promote this tourist attraction. This research is a preliminary study of how the best strategy for developing a tourist attraction with the main goal of tourists. The approach taken is qualitative, with reference to the theory of creativity and promotion theory Tour. In order to spread evenly, and obtain comprehensive data, the focus of the research is on Blangsinga Waterfall, Saba Village, Blahbatuh District, Gianyar Regency. Data will be collected through interviews, literature studies are expected, academically, this research is able to examine and explore more deeply with respect to the background, socialization patterns that are applied, and their implications for the local community as well as tourists, especially those visiting Blangsinga Waterfall, Saba Village. , Blahbatuh District, Gianyar Regency. Then it is also expected to be one of the contributions of thought in developing innovative, creative, and sustainable culture-based tourism.